2003
DOI: 10.1093/emboj/cdg139
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the NF-kappaB p65 subunit by mitogen- and stress-activated protein kinase-1 (MSK1)

Abstract: Nuclear factor kB (NF-kB) is one of the key regulators of transcription of a variety of genes involved in immune and in¯ammatory responses. NF-kB activity has long been thought to be regulated mainly by IkB family members, which keep the transcription factor complex in an inactive form in the cytoplasm by masking the nuclear localization signal. Nowadays, the importance of additional mechanisms controlling the nuclear transcription potential of NF-kB is generally accepted. We show that the mitogen-activated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
628
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 693 publications
(656 citation statements)
references
References 67 publications
26
628
2
Order By: Relevance
“…It has been reported that p38 MAPK is required for NF-kB-driven gene transcription in response to TNFa 47 and can critically affect NF-kB activation. 48,49 However, since sensitization of NHU cells occurred mainly following inhibition of NF-kB and the p38 MAPK inhibitor preferentially increased tumor cell susceptibility to TRAIL, it is unlikely that p38 MAPK functions solely along the NF-kB signaling axis in either normal or malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that p38 MAPK is required for NF-kB-driven gene transcription in response to TNFa 47 and can critically affect NF-kB activation. 48,49 However, since sensitization of NHU cells occurred mainly following inhibition of NF-kB and the p38 MAPK inhibitor preferentially increased tumor cell susceptibility to TRAIL, it is unlikely that p38 MAPK functions solely along the NF-kB signaling axis in either normal or malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…GCinduced expression of DUSP1 is accompanied by a decrease in phosphorylation of nuclear c-Jun Zhou et al, 2007), with consequences that may be indistinguishable from classical A Clark Anti-inflammatory functions of glucocorticoid-induced genes Page 21 of 53 transrepression of AP1. The p38 MAPK pathway can influence the transcriptional activation properties of NFκB (Vermeulen et al, 2003) or its recruitment to binding sites in promoters of pro-inflammatory genes (Saccani et al, 2002). A bacterially encoded dual-specificity phosphatase that targets p38 MAPK inhibits the transcriptional activation of certain NFκB-dependent promoters (Arbibe et al, 2007), and it is tempting to speculate that DUSP1 may have similar effects.…”
Section: A Clarkmentioning
confidence: 99%
“…These MAPK subtypes are constitutively expressed in articular chondrocytes and transiently activated by numerous stimuli, including IL-1␤ and tumor necrosis factor ␣ (TNF␣) (13). Several studies suggest that MAPKs are also able to modulate the IL-1␤-induced NF-B pathway (14). NF-B normally exists as an inactive cytoplasmic complex, the predominant form of which is a heterodimer composed of p50 and p65 (RelA) subunits, bound to inhibitory proteins of the I B family.…”
mentioning
confidence: 99%